A mixed-methods study to identify effective practices in the teaching of writing in a digital learning environment in low income schools. (April 2018) - Jesson, Rebecca; McNaughton, Stuart; Rosedale, Naomi; Zhu, Tong; Cockle, Victoria
Abstract: This paper reports on the teaching practices identified as effective for students' writing progress in a digital learning environment. The study is situated within a design-based research partnership between researchers and a group of urban schools serving culturally diverse students from low income communities who have implemented a digital pedagogy innovation which includes student device ownership, wireless access and a shared pedagogical approach. The research design logic was to select demonstrably effective teachers as 'case studies' in order to understand what effective teachers in the innovation did that promoted greater progress in writing. Qualitative analyses of selected teachers' class sites and students' individual blogs identified features of teaching practice hypothesised to promote student development in writing. To strengthen our understandings, teachers were interviewed to check the comprehensiveness and validity of our interpretation. Classroom observations from these case study teachers were compared with observations from a larger group of teachers to investigate whether identified practices were differentially employed by these effective teachers. Finally, the effects on student writing achievement of the relative presence of these practices in all observed classes were predicted using a hierarchical linear model. Our findings indicate effects of using digital tools in ways that promote complex compositional tasks, discussion and critical thinking. The study adds to a growing number of studies that investigate the nature of effective pedagogy within a digital environment. It contributes to the identification of promising practices for the design of more effective instruction in writing within classes that have ubiquitous digital access. Highlights: Students wrote more often, used open ended templates and composed digital learning objects. Students engaged in discussions requiring critical thinking or critical literacy. Students were less often given constrained practice tasks such as worksheets or games.